Macromol. Chem. Phys. 3/2014. Issue 3 (February 2014) - Raue, M.; Wambach, M.; Glöggler, S.; Grefen, D.; Kaufmann, R.; Abetz, C.; Georgopanos, P.; Handge, U. A.; Mang, T.; Blümich, B.; Abetz, V.
<x xml:space="preserve">Abstract</x> Front Cover: In this work, original hard rubbery ornaments produced by Charles Goodyear are investigated and compared with a natural rubber sample produced according to US patent 3633 for reference. Contrary to expectation, it is found that Charles Goodyear did not use white lead in the investigated chain segment. The reproduced samples are artificially aged and investigated using an NMR‐MOUSE, FTIR spectroscopy, SEM‐EDX, and rheological methods. The NMR‐MOUSE is found to be particularly suited for studying valuable objects because it is a tool that provides information about the aging process in a non‐destructive way. Further details can be found in the article by M. Raue, M. Wambach, S. Glöggler, D. Grefen, R. Kaufmann, C. Abetz, P. Georgopanos, U. A. Handge, T. Mang, B. Blümich, * and V. Abetz* on page 245. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>